2017
DOI: 10.1038/s41598-017-09059-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell damage produced by magnetic fluid hyperthermia on microglial BV2 cells

Abstract: We present evidence on the effects of exogenous heating by water bath (WB) and magnetic hyperthermia (MHT) on a glial micro-tumor phantom. To this, magnetic nanoparticles (MNPs) of 30–40 nm were designed to obtain particle sizes for maximum heating efficiency. The specific power absorption (SPA) values (f = 560 kHz, H = 23.9 kA/m) for as prepared colloids (533–605 W/g) dropped to 98–279 W/g in culture medium. The analysis of the intracellular MNPs distribution showed vesicle-trapped MNPs agglomerates spread al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 68 publications
6
44
0
Order By: Relevance
“…Likewise, Wilhelm et al 12 obtained similar results for human prostatic tumor cells (PC3). Also, even Calatayud et al's 13 group mentioned above, in another comprehensive work, found no differences in viability of microglial BV2 cells subjected to hyperthermia induced by homogeneous water bath heating or a magnetically triggered one, contradicting apparent results obtained previously in other experimental conditions. 10 In this work, in order to shed some light on these seemingly inconsistent reports, we tested the comparative efficiency of WHT and MHT delivered by Fe-Cr-Nb-B magnetic nanoparticles with controllable Curie temperature 14 on commercial human osteosarcoma (hOS), MG-63 cell line (purchased from Sigma-Aldrich company, St Louis, MO, USA).…”
Section: Introductionmentioning
confidence: 68%
“…Likewise, Wilhelm et al 12 obtained similar results for human prostatic tumor cells (PC3). Also, even Calatayud et al's 13 group mentioned above, in another comprehensive work, found no differences in viability of microglial BV2 cells subjected to hyperthermia induced by homogeneous water bath heating or a magnetically triggered one, contradicting apparent results obtained previously in other experimental conditions. 10 In this work, in order to shed some light on these seemingly inconsistent reports, we tested the comparative efficiency of WHT and MHT delivered by Fe-Cr-Nb-B magnetic nanoparticles with controllable Curie temperature 14 on commercial human osteosarcoma (hOS), MG-63 cell line (purchased from Sigma-Aldrich company, St Louis, MO, USA).…”
Section: Introductionmentioning
confidence: 68%
“…[21][22][23] Currently, most of the in vitro studies that analyse the efficacy of the hyperthermia treatment are being performed in monolayer cell cultures. [24][25][26] However, this traditional cell culture method, in two dimensions (2D), has essential limitations in terms of inter-cellular communication, cell microenvironment and cell spatial behaviour. 27 Therefore, these 2D cell culture models cannot replicate the morphology and biochemical properties the cells have in the living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve maximum therapeutic effects, the function of antigenicity, adjuvanticity, and feedback inhibition, three important factors in reactivating an antitumor immune response, should be comprehensively coordinated when designing efficient collaborative strategies . Tailoring biomaterials to integrate multiple other therapies such as gene therapy, cell therapy, magnetic fluid hyperthermia, and so on will provide great promise in the development of ICB therapy. Considering the relatively low response rate associated with ICB, identification of predictive and pharmacodynamic biomarkers will be crucial to guide the choice of inhibitor .…”
Section: Resultsmentioning
confidence: 99%